1988
DOI: 10.1029/pa003i001p00001
|View full text |Cite
|
Sign up to set email alerts
|

The chronology of the last Deglaciation: Implications to the cause of the Younger Dryas Event

Abstract: It has long been recognized that the transition from the last glacial to the present interglacial was punctuated by a brief and intense return to cold conditions. This extraordinary event, referred to by European palynologists as the Younger Dryas, was centered in the northern Atlantic basin. Evidence is accumulating that it may have been initiated and terminated by changes in the mode of operation of the northern Atlantic Ocean. Further, it appears that these mode changes may have been triggered by diversions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
126
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(137 citation statements)
references
References 41 publications
8
126
0
3
Order By: Relevance
“…A pulse of fresh water (glacial melt water) into the North Atlantic is believed to have caused this anomaly via affects on the THC (Broecker et al 1988;Bard et al 1990;Hughen et al 2000). The response and stability of the THC in HadCM3 to both fresh water and anthropogenic forcing have been explored in previous studies (Thorpe et al 2001;.…”
Section: (B) Climate Scenarios and Simulationsmentioning
confidence: 99%
“…A pulse of fresh water (glacial melt water) into the North Atlantic is believed to have caused this anomaly via affects on the THC (Broecker et al 1988;Bard et al 1990;Hughen et al 2000). The response and stability of the THC in HadCM3 to both fresh water and anthropogenic forcing have been explored in previous studies (Thorpe et al 2001;.…”
Section: (B) Climate Scenarios and Simulationsmentioning
confidence: 99%
“…Several authors have investigated this issue for past climates and future climate projections. The discharge of meltwater from the northern hemisphere ice sheets has been proposed as the triggering mechanism for abrupt climate change in the past at the time of the Younger Dryas (Broecker et al 1988;Maier-Reimer and Mikolajewicz 1989). Fichefet et al (2003) found a substantial weakening of the NAMOC in response to increased meltwater fluxes from the GrIS in a twenty-first century simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Initial support for this theory included elevated δ 18 O values in Gulf of Mexico sediment dating from the early YD (implying that meltwater was rerouted elsewhere) (Broecker et al, 1988;Flower and Kennett, 1990;Teller, 1990). The meltwater was originally proposed to have travelled to the North Atlantic via the St Lawrence Valley, but results have so far revealed only limited geological evidence of a massive flux of freshwater coincident with the YD initiation (Broecker, 2006a;Rayburn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Initial support for this theory included elevated δ 18 O values in Gulf of Mexico sediment dating from the early YD (implying that meltwater was rerouted elsewhere) (Broecker et al, 1988;Flower and Kennett, 1990;Teller, 1990). The meltwater was originally proposed to have travelled to the North Atlantic via the St Lawrence Valley, but results have so far revealed only limited geological evidence of a massive flux of freshwater coincident with the YD initiation (Broecker, 2006a;Rayburn et al, 2011). The freshwater pulse may have followed another route to the ocean, and other research has proposed the Mackenzie Valley (Condron and Winsor, 2012;Murton et al, 2010) as a possible alternative and the Fennoscandian Ice Sheet as an alternate source .…”
Section: Introductionmentioning
confidence: 99%